IFN-γ-mediated suppression of coronavirus replication in glial-committed progenitor cells - Whitman, Lucia (Elsevier Inc., 2009)
The neurotropic JHM strain of mouse hepatitis virus (JHMV) replicates primarily within glial cells following intracranial inoculation of susceptible mice, with relative sparing of neurons. This study demonstrates that glial cells derived from neural progenitor cells are susceptible to JHMV infection and that treatment of infected cells with IFN-γ inhibits viral replication in a dose-dependent manner. Although type I IFN production is muted in JHMV-infected glial cultures, IFN-β is produced following IFN-γ-treatment of JHMV-infected cells. Also, direct treatment of infected glial cultures with recombinant mouse IFN-α or IFN-β inhibits viral replication. IFN-γ-mediated control of JHMV replication is dampened in glial cultures derived from the neural progenitor cells of type I receptor knock-out mice. These data indicate that JHMV is capable of infecting glial cells generated from neural progenitor cells and that IFN-γ-mediated control of viral replication is dependent, in part, on type I IFN secretion.